Human platelet lysates-based hydrogels: a novel personalized 3d platform for spheroid invasion assessment - Monteiro, Cátia F. (2022)
Fundamental physiologic and pathologic phenomena such as wound healing and cancer metastasis are typically associated with the migration of cells through adjacent extracellular matrix. In recent years, advances in biomimetic materials have supported the progress in 3D cell culture and provided biomedical tools for the development of models to study spheroid invasiveness. Despite this, the exceptional biochemical and biomechanical properties of human-derived materials are poorly explored. Human methacryloyl platelet lysates (PLMA)-based hydrogels are herein proposed as reliable 3D platforms to sustain in vivo-like cell invasion mechanisms. A systematic analysis of spheroid viability, size, and invasiveness is performed in three biomimetic materials: PLMA hydrogels at three different concentrations, poly(ethylene glycol) diacrylate, and Matrigel. Results demonstrate that PLMA hydrogels perfectly support the recapitulation of the tumor invasion behavior of cancer cell lines (MG-63, SaOS-2, and A549) and human bone-marrow mesenchymal stem cell spheroids. The distinct invasiveness ability of each cell type is reflected in the PLMA hydrogels and, furthermore, different mechanical properties produce an altered invasive behavior. The herein presented human PLMA-based hydrogels could represent an opportunity to develop accurate cell invasiveness models and open up new possibilities for humanized and personalized high-throughput screening and validation of anticancer drugs.